NaHS alleviates neuropathic pain in mice by inhibiting IL-17-mediated dopamine (DA) neuron necroptosis in the VTA - Jun Wang; Nan Zhang; Hong-Zheng Liu; Jin-Liang Wang; Yong-Bo Zhang; Dong-Dong Su; Li-Min Zhang; Bao-Dong Li; Hui-Tao Miao; Jun Miao (Brain Research Bulletin)
Background: Neuropathic pain (NP) constitutes a significant burden for individuals, manifesting as nociceptive anaphylaxis, hypersensitivity, and spontaneous pain. Previous research has suggested that the analgesic effects of NP are mediated by dopamine (DA) neurons in the ventral tegmental region (VTA) through projections to various brain regions. A decrease in VTA dopamine neurons following NP may contribute to prolonged pain. It has been revealed that inflammatory activation triggers necroptosis by stimulating mixed lineage kinase domain-like protein (MLKL), leading to progressive neuronal demise. Recent research from many studies has revealed that IL-17-induced necroptosis plays an important role in neuroinflammation and neuronal damage. To our knowledge, few studies have hitherto investigated how IL-17-induced necroptosis may contribute to neuropathic pain. Hydrogen sulfide (H2S) treatment is commonly used for neuropathic pain, although the exact mechanisms remain unclear. Sodium hydrosulfide (NaHS), a common H2S delivery method in medicine, has also been shown to exert neuroprotective effects against neuropathic pain. This study aimed to investigate the link between IL-17-induced necroptosis of dopamine neurons in the VTA and neuropathic pain. Additionally, we explored whether H2S treatment could reduce the loss of VTA dopamine neurons, thereby lowering neuropathic pain in a chronic constriction injury (CCI) model. Methods: This study employed a CCI animal model created using a sciatic nerve ligation approach. To investigate the effect of H2S treatment on neuropathic pain, NaHS was injected intrathecally into CCI model mice. The thermal withdrawal latency (TWL) and mechanical withdrawal threshold (MWT) were evaluated to assess the mice's pain thresholds. Additional experiments, including electrophysiological studies and immunofluorescence assays, western blotting, real-time quantitative Polymerase Chain Reaction (PCR) were conducted to elucidate the precise mechanism underlying the analgesic effects of H2S therapy on neuropathic pain. Results: In mice exposed to CCI, there was a significant decrease in dopamine neurons, a reduction in MWT and TWL, decreased expression of tyrosine hydroxylase (TH) protein and TH mRNA and an increase in VTA firing rate and MLKL colocalization with DA neurons (all p < 0.05). However, treatment with NaHS remarkably restored these changes. Additionally, IL-17 administration negated the neuroprotective benefit of H2S after CCI. Conclusion: H2S therapy reduces CCI-induced neuropathic pain in mice. This protective mechanism may be linked to the prevention of IL-17-induced necroptosis of dopamine neurons in the VTA.